HUBUNGAN ANTARA NILAI-NILAI ETIKA DALAM FILSAFAT PENDIDIKAN DAN KETERLIBATAN SOSIAL MAHASISWA DI UNIVERSITAS BINA BANGSA - Saepudin Malik; Desty Endrawati Subroto; Salsabila Krisna Hermanto; Farha Rizqi Imara; Insania Khoiriyah (CV. Denasya Smart Publisher, 2025)
This research aims to examine the relationship between ethical values ​​in educational philosophy and students' social involvement in higher education. Through a literature review and qualitative data analysis, this research reveals that ethical values ​​such as justice, responsibility and empathy embedded in educational philosophy have a significant influence on students' motivation and actions in participating in social activities. Students who have a strong understanding of ethical values ​​tend to be more proactive in making positive contributions to society